Grease deoxidation catalyst with high high-temperature catalytic activity as well as preparation method and application of grease deoxidation catalyst
The one-step preparation of nickel nitrate, cobalt nitrate and titanium dioxide is achieved to form a high-temperature active nickel cobalt catalyst, which solves the problems of high catalyst cost and complex production process in the prior art, and achieves efficient biofuel deoxygenation in non-hydrogen environments, improving the The deoxygenation efficiency and selectivity of biofuels are achieved.
Patent Information
- Application Number
- CN202411269372.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-07
AI Technical Summary
Prior art In the preparation of biofuel, transition metal catalysts are costly and cumbersome in production, making it difficult to meet the needs of deoxygenation and isomerization under high temperature conditions, especially without introducing hydrogen.
Using nickel nitrate and cobalt nitrate as metal sources, combined with 5-10nm hydrophilic lipophilic titanium dioxide as support, nickel cobalt bimetallic catalyst was prepared by one-step method, and using magnetic stirring and inert gas decomposition technology to form a biological with high temperature catalytic activity. Fuel deoxygenation catalyst.
The high-temperature deoxygenation bond-breaking reaction of oxygen-containing oils in a non-hydrogen environment is realized, which reduces the use and cost of hydrogen, improves the deoxygenation efficiency and selectivity of biofuel, and the particle size of the catalyst is uniformly distributed, and the specific surface area of the BET reaches 75-85m2. /g, the deoxygenation efficiency can reach more than 83%, and the selectivity can reach more than 44%.
Smart Images

Figure CN119259051A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biofuel preparation, and in particular relates to a grease deoxidation catalyst with excellent high-temperature catalytic activity, a preparation method and application thereof. Background Art
[0002] Biofuel has the advantages of being green, having high energy density, high calorific value, high energy utilization efficiency and a wide range of raw material sources. It is of great significance for the aviation industry to effectively reduce greenhouse gas emissions and is regarded as a clean energy with great application prospects. Therefore, the catalyst required for biofuel preparation is very important. The scale economy, efficient preparation, production and conversion technologies will directly affect the large-scale use of biofuel technology.
[0003] In recent years, aviation biofuel raw materials include animal and plant oils, cellulose, biomass sugar, microalgae, etc. Among them, animal and plant oil-based biofuel is the most technologically mature product at present. It is mainly produced from raw materials such as palm oil, rapeseed oil, and catering waste oil. It has the advantages of high energy density and molecular structure close to aviation biofuel, and can achieve a 50% blending degree of fossil jet fuel. Compared with traditional jet fuel, biofuel can reduce carbon dioxide emissions by 55%-92%. It is not only renewable and sustainable, but also does not require engine modification. Using catering waste oil to produce biofuel can avoid the problem of excessively high raw material costs (accounting for 75% to 80% of supply chain costs) and reduce the adverse effects of improper disposal of catering waste oil on the environment.
[0004] Due to the shortage and high cost of precious metals, the development of non-precious metal catalysts has become increasingly important. Among non-precious metal catalysts, transition metals are potential choices for producing biofuels from fatty acids due to their strong redox potential. Currently, commonly used deoxygenation catalysts are mainly composed of transition metals (such as Pd, Pt, Cu, Co, Ru and Ni) or metal sulfide catalysts (such as MoS2, NiMoS2 and CoMoS2). Pd and Pt catalysts are expensive and their catalytic activity is difficult to further improve. Therefore, the research and development of non-precious metal catalysts suitable for deoxygenation and isomerization of oxygenated oils and fats has received widespread attention. Studies have shown that nickel-based catalysts show excellent catalytic activity and can be used as monometallic or bimetallic catalysts, but due to the synergistic effect of metals, bimetallic nickel-based catalysts show good biofuel conversion performance.
[0005] Zhou et al. synthesized Co / ZrO2 catalyst supported by ZrO2 by incipient wetness impregnation method and analyzed the ability of ethyl palmitate to convert into alcohols or diesel alkanes. Under hydrogen atmosphere at 240℃, the reaction time was 8 hours, and the alkanes yield after decarbonylation and hydrodeoxygenation reaction was 82%. (Temperature-tuned selectivity to alkanes oralcohol from ethyl palmitate deoxygenation over zirconia-supported cobaltcatalyst[J].Fuel,2020,278,(118295))
[0006] According to the above literature reports, the current preparation route of transition metal-supported titanium dioxide catalysts is that the single metal first forms a uniform solution, then loads the carrier, and then obtains a single metal-based catalyst after calcination and reduction. In addition, the introduction of different liquid phases and the calcination and reduction process with gases such as hydrogen during the preparation process are cumbersome and time-consuming, which increases the production cost of the catalyst and generates more waste, which is not conducive to environmental protection. In addition, the prepared single metal-based catalyst cannot meet the current needs of deoxidation and isomerization.
[0007] Patent application 202310353949.9 discloses a supported FeNi bimetallic catalyst and its preparation method and application, the preparation method comprising the following steps: (1) adding a carrier and a metal precursor to deionized water, stirring and drying; (2) calcining under an argon atmosphere; (3) reducing under a 5% hydrogen / argon atmosphere; (4) placing the catalyst and fatty acid in a micro-batch reactor to evaluate performance. The supported FeNi catalyst prepared by the present invention has good deoxidation activity and stability due to the synergistic effect and electronic modification of the bimetallic. This invention patent has the disadvantage of excessive FeNi metal loading, which leads to an increase in the cost of catalyst preparation. In addition, a two-step calcination method is adopted to introduce hydrogen during the calcination process, increase the consumption of hydrogen energy, and make the catalytic process H2-dependent. In this invention, stearic acid is used as the research object. During the research process, the amount of catalyst used in the stearic acid conversion process is relatively high, which is not conducive to the research of high-efficiency catalysts.
[0008] Therefore, it is necessary to develop a simple method for preparing titanium dioxide-supported bimetallic nickel-cobalt catalysts, and the catalysts prepared by this method should also have excellent high-temperature catalytic activity. Summary of the invention
[0009] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a catalyst for oil deoxygenation with high catalytic activity under high temperature conditions and its preparation method and application, without the need to introduce hydrogen during the deoxygenation and isomerization process of oxygenated oils.
[0010] The purpose of the present invention can be achieved by the following technical solutions:
[0011] The invention provides a biofuel deoxidation catalyst, which comprises an active component, a carrier and an auxiliary agent. The active component is metal nickel and cobalt, and the carrier is titanium dioxide.
[0012] Furthermore, the active components of the catalyst are made of nickel nitrate and cobalt nitrate, and the mass ratio of nickel nitrate to cobalt nitrate is (1-3):(1-2).
[0013] Furthermore, the mass ratio of the metal nitrate to the titanium dioxide is 1:5. Furthermore, the carrier is a 5-10 nm hydrophilic and lipophilic titanium dioxide.
[0014] In another aspect, the present invention provides a method for preparing the above-mentioned biofuel deoxygenation catalyst, comprising the following steps:
[0015] (1) dissolving nickel nitrate and cobalt nitrate to obtain a metal salt mixed solution;
[0016] (2) Mixing the metal salt mixed solution obtained in step (1) with nano titanium dioxide and drying to obtain a metal salt titanium dioxide mixed powder
[0017] (3) Decomposing the metal salt titanium dioxide mixed powder obtained in step (2) under an inert gas to obtain a biofuel deoxidation catalyst.
[0018] Furthermore, the drying temperature in step (2) is 50-150° C., and the drying time is 10-14 h.
[0019] Furthermore, the inert gas used for decomposition under inert gas in step (3) is nitrogen, the decomposition temperature is 400-600° C., and the decomposition time is 3-5 h.
[0020] Furthermore, the step (1) of dissolving nickel nitrate and cobalt nitrate is specifically as follows:
[0021] Nickel nitrate and cobalt nitrate are placed in a container, deionized water is added, and the mixture is stirred at a stirring speed of 100-300 r / min for 1-3 hours to obtain a metal salt mixed solution.
[0022] In the third aspect, the present invention also provides an application of the above-mentioned biofuel deoxygenation catalyst in biofuel production, that is, under the conditions that the raw gas is nitrogen, the gas flow rate is 250mL / min, the reaction temperature is 300-400°C, and the catalyst is used to deoxygenate catering waste oil to obtain biofuel.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1) The present invention aims to solve the defect that hydrogen needs to be introduced in the deoxygenation and isomerization process of conventional oxygenated oils and fats; cobalt nitrate and nickel nitrate are used as metal sources, and the bond breaking ability and isomerization ability of cobalt and nickel for oils and fats are utilized. At the same time, 5-10nm hydrophilic and lipophilic titanium dioxide is used as a carrier to design a bifunctional catalyst, so that the catalyst product can show excellent high-temperature activity for the deoxygenation and bond breaking reaction of oxygenated oils and fats in a non-hydrogen environment, reduce the use of hydrogen and the corresponding cost, further promote the popularization and application of biofuels, and comply with the current market demand driven by reducing carbon dioxide emissions.
[0025] 2) The particle size of the catalyst of the present invention is mainly distributed in the range of 11-13 nm, and the BET specific surface area can reach 75-85 m 2 / g, and exhibits excellent high-temperature activity for the deoxygenation and bond-breaking reaction of oxygenated oils and fats. Under the conditions of nitrogen as the raw gas and a gas flow rate of 250mL / min, the deoxygenation efficiency at a reaction temperature of 300-400℃ can reach more than 83%, and the biofuel selectivity at 350℃ can reach more than 44%.
[0026] 3) The present invention magnetically stirs nickel nitrate and cobalt nitrate to obtain a metal salt mixed solution; fully mixes nano titanium dioxide with the metal salt mixed solution; decomposes the metal salt and titanium dioxide mixture to obtain the biofuel deoxygenation catalyst under an inert gas environment. The present invention uses two specific metal salts, nickel nitrate and cobalt nitrate, as reaction raw materials. Since the two metal salts are both inorganic metal salts formed by metal cations and nitrate ions, they have similar molecular structures or crystal structures and physical and chemical properties. Through magnetic stirring, they are easier to achieve uniform dispersion at the nanometer level or even the molecular level and atomic level. At the same time, the present invention adds titanium dioxide through a "one-step method" to make the metal nickel and cobalt load and dispersion higher.
[0027] 4) The present invention uses a "one-step method" to add specific raw materials cobalt nitrate and nickel nitrate, and uses magnetic stirring to mix the materials at the nanometer level to produce fine particles with a large specific surface area, and then decomposes and decomposes with an inert gas to obtain the biofuel deoxygenation catalyst. The several steps cooperate with each other to greatly reduce the catalyst particle size, improve the high-temperature activity of the catalyst and the degree of dispersion of the metal. The particle size of the product obtained by decomposition is further changed using a mortar, and defects and new interfaces are generated in the material during the grinding process, so that a catalyst with relatively uniform particle size and good dispersion is obtained. Compared with the existing preparation method, the one-step synthesis, the titanium dioxide carrier-loaded nickel and cobalt to obtain the nickel-cobalt / titanium dioxide catalyst, has fewer operating procedures and a short preparation cycle, and no solvent is used in the process, and no waste liquid is generated. It is a simpler and easier to operate preparation method. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Example 1 of the present invention;
[0029] Figure 2 is a graph of the specific surface area of the biofuel deoxygenation catalyst prepared in Example 1 of the present invention;
[0030] Figure 3 is a scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Example 2 of the present invention;
[0031] Figure 4 is a graph of the specific surface area of the biofuel deoxygenation catalyst prepared in Example 2 of the present invention;
[0032] Figure 5 is a scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Example 3 of the present invention;
[0033] Figure 6 is a graph of the specific surface area of the biofuel deoxygenation catalyst prepared in Example 3 of the present invention;
[0034] Figure 7 is a scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Example 4 of the present invention;
[0035] Figure 8 is a graph of the specific surface area of the biofuel deoxygenation catalyst prepared in Example 4 of the present invention;
[0036] Fig. 9 is a scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Comparative Example 1 of the present invention;
[0037] Fig.10 This is a specific surface area diagram of the biofuel deoxygenation catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0039] The invention provides a biofuel deoxygenation catalyst, which comprises an active component, a carrier and an auxiliary agent. The active component is metal nickel, the carrier is titanium dioxide, and the auxiliary agent is metal cobalt. The mass of nickel and cobalt nitrate accounts for 10-20wt.% of the mass of the catalyst, and the titanium dioxide accounts for 80-90wt.% of the mass of the catalyst. The active component of the catalyst uses nickel nitrate as a raw material, and the auxiliary agent uses cobalt nitrate as a raw material. The mass ratio of nickel nitrate to cobalt nitrate is (1-3):(1-2). The carrier uses 5-10nm hydrophilic and lipophilic titanium dioxide.
[0040] The above-mentioned biofuel deoxygenation catalyst is prepared by the following method:
[0041] S1, dissolving nickel nitrate and cobalt nitrate in a mass ratio of (1-3):(1-2) in deionized water, placing in a magnetic stirrer, rotating at a speed of 100-300 r / min, stirring for 1-3 h, to obtain a metal salt mixed solution.
[0042] S2, stirring and mixing the obtained metal salt mixed solution and nano-sized titanium dioxide, and placing in an oven at 100° C. in an air atmosphere to dry for 10-14 hours.
[0043] S3, after drying, the mixture powder is transferred to a crucible, and placed in a tube furnace for further decomposition under a nitrogen environment, the decomposition temperature is set to 400-600°C, and the decomposition time is 3-5 hours. After the decomposition is completed, the mixture powder is crushed in a mortar and sieved to obtain a granular mixture, which is the biofuel deoxidation catalyst.
[0044] The obtained catalyst can be used to produce biofuel, such as using the prepared biofuel deoxygenation catalyst to deoxygenate restaurant waste oil to obtain biofuel, which can be used as aviation biofuel raw material together with other raw materials in the production of aviation biofuel.
[0045] The raw materials and equipment used in the present invention are all conventional raw materials and equipment in the art. In the following embodiments, raw materials or processing techniques, unless otherwise specified, are all conventional commercially available raw materials or conventional processing techniques in the art.
[0046] For example, the 5-10 nm hydrophilic and lipophilic titanium dioxide used in the present invention is selected from Shanghai MacLean Biochemical Technology Co., Ltd., and the cobalt nitrate hexahydrate and nickel nitrate hexahydrate are selected from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0047] In the following examples, waste cooking oil (which does not require further purification) generated after frying food in ordinary domestic restaurants is used as an example, and the catalyst of the present invention is used to treat it to produce biofuel as a raw material for aviation biofuel.
[0048] Example 1
[0049] A method for preparing a biofuel deoxygenation catalyst is as follows:
[0050] ① Dissolve 0.67 g nickel nitrate and 1.33 g cobalt nitrate in 6 mL of deionized water, place in a magnetic stirrer, rotate at 200 r / min, and stir for 2 h to obtain a metal salt mixed solution.
[0051] ② The obtained metal salt mixture was evenly stirred with 10 g of nano-sized titanium dioxide, and then placed in an oven at 100° C. and dried in air atmosphere for 12 h.
[0052] ③ After drying, the mixture powder is transferred to a crucible and placed in a tubular furnace under a nitrogen environment for further decomposition. The decomposition temperature is set to 500°C and the decomposition time is 4 hours. After the decomposition is completed, the mixture powder is crushed in a mortar and sieved to obtain a granular mixture, which is the biofuel deoxygenation catalyst.
[0053] 5 g of the obtained biofuel deoxygenation catalyst was weighed and placed in a three-necked flask, nitrogen was introduced (the nitrogen introduction rate was 250 mL / min), 100 g of waste cooking oil was added, the reaction temperature was set to 350° C., and the reaction time was 2 h.
[0054] The surface structure of the NiCo (1:2) catalyst prepared above was scanned by scanning electron microscopy. Figure 1 As shown in the figure. The scanning electron microscope image shows that the particle size distribution of the NiCo(1) catalyst is relatively uniform, but there is obvious particle agglomeration, which may be mainly due to the influence of high temperature conditions. The specific surface area tester was used to analyze the obtained catalyst and the titanium dioxide used as the carrier. The specific surface area of the catalyst was 78.081m 2 / g, with an average pore size of 12.281nm and a void volume of 0.353cm 3 / g, its specific surface area is shown in the figure Figure 2 As shown in Table 2. Compared with the specific surface area of pure titanium dioxide 84.438m 2 / g decreased, and the main reason may be that the introduction of bimetallic particles caused agglomeration and increased the particle size of nanoparticles.
[0055] Example 2
[0056] This embodiment provides a method for preparing a biofuel deoxygenation catalyst, and the specific method is as follows:
[0057] ① Dissolve 1g nickel nitrate and 1g cobalt nitrate in 6mL of deionized water, place in a magnetic stirrer, rotate at 200r / min, stir for 2h, and obtain a metal salt mixed solution.
[0058] ② The obtained metal salt mixture was evenly stirred with 10 g of nano-sized titanium dioxide, and then placed in an oven at 100° C. and dried in air atmosphere for 12 h.
[0059] ③ After drying, the mixture powder is transferred to a crucible and placed in a tubular furnace under a nitrogen environment for further decomposition. The decomposition temperature is set to 500°C and the decomposition time is 4 hours. After the decomposition is completed, the mixture powder is crushed in a mortar and sieved to obtain a granular mixture, which is the biofuel deoxygenation catalyst.
[0060] 5 g of the obtained biofuel deoxygenation catalyst was weighed and placed in a three-necked flask, nitrogen was introduced (the nitrogen introduction rate was 250 mL / min), 100 g of waste cooking oil was added, the reaction temperature was set to 350° C., and the reaction time was 2 h.
[0061] The surface structure of the NiCo (1:1) catalyst prepared above was scanned by scanning electron microscopy. Figure 3 The catalyst particle size is relatively uniform, and due to high temperature decomposition, the catalyst shows obvious agglomeration. The specific surface area tester was used to analyze the particle size of the obtained catalyst and the titanium dioxide as a carrier. The specific surface area of the catalyst is 77.521m 2 / g, with an average pore diameter of 12.266nm and a void volume of 0.359cm 3 / g, its specific surface area data is as follows Figure 4 As shown in Table 2. The main reason is that the introduction of bimetallic particles increases the particle size of nanoparticles and reduces the specific surface area.
[0062] Example 3
[0063] This embodiment provides a method for preparing a biofuel deoxygenation catalyst, and the specific method is as follows:
[0064] ① Dissolve 1.33 g nickel nitrate and 0.67 g cobalt nitrate in 6 mL deionized water, place in a magnetic stirrer, rotate at 200 r / min, stir for 2 h, and obtain a metal salt mixed solution.
[0065] ② The obtained metal salt mixture was evenly stirred with 10 g of nano-sized titanium dioxide, and then placed in an oven at 100° C. and dried in air atmosphere for 12 h.
[0066] ③ After drying, the mixture powder is transferred to a crucible and placed in a tubular furnace for further decomposition under a nitrogen environment. The decomposition temperature is set to 500°C and the decomposition time is 4 hours. After the decomposition is completed, the mixture powder is crushed and sieved in a mortar to obtain a granular mixture, which is the biofuel deoxygenation catalyst. Weigh 5g of the obtained biofuel deoxygenation catalyst and place it in a three-necked flask. Nitrogen is introduced (the nitrogen introduction rate is 250mL / min), 100g of catering waste oil is added, the reaction temperature is set to 350°C, and the reaction time is 2 hours.
[0067] The surface structure of the NiCo (2:1) catalyst prepared above was scanned by scanning electron microscopy. Figure 5 As shown. The catalyst scanning electron microscope image shows poor uniformity of particle size due to the use of impregnation. High temperature decomposition leads to obvious agglomeration of the catalyst. The particle size of the obtained catalyst and the titanium dioxide as a carrier was analyzed using a specific surface area tester. The specific surface area of the catalyst is 74.735m 2 / g, with an average pore diameter of 12.261nm and a void volume of 0.346cm 3 / g, its specific surface area data is as follows Figure 6 As shown in Table 2. The change in specific surface area is mainly due to the introduction of bimetallic particles, which causes the agglomeration of nanoparticles and increases the particle size, while the average pore size remains basically unchanged, proving that the introduction of bimetallic particles does not affect the pore size of the carrier titanium dioxide.
[0068] Example 4
[0069] This embodiment provides a method for preparing a biofuel deoxygenation catalyst, and the specific method is as follows:
[0070] ① Dissolve 1.20 g of nickel nitrate and 0.80 g of cobalt nitrate in 6 mL of deionized water, place in a magnetic stirrer, rotate at 200 r / min, and stir for 2 h to obtain a metal salt mixed solution.
[0071] ② The obtained metal salt mixture was mixed evenly with 10 g of nano-sized titanium dioxide, and dried in an oven at 100° C. in air atmosphere for 12 h.
[0072] ③ After drying, the mixture powder is transferred to a crucible and placed in a tubular furnace for further decomposition under a nitrogen environment. The decomposition temperature is set to 500°C and the decomposition time is 4 hours. After the decomposition is completed, the mixture powder is crushed and sieved in a mortar to obtain a granular mixture, which is the biofuel deoxygenation catalyst. Weigh 5g of the obtained biofuel deoxygenation catalyst and place it in a three-necked flask. Nitrogen is introduced (the nitrogen introduction rate is 250mL / min), 100g of catering waste oil is added, the reaction temperature is set to 350°C, and the reaction time is 2 hours.
[0073] The surface structure of the NiCo (3:2) catalyst prepared above was scanned by scanning electron microscopy. Figure 7 As shown in the figure, the particle size of the obtained catalyst and the titanium dioxide as a carrier was analyzed by a specific surface area tester, wherein the specific surface area of the catalyst was 75.793 m 2 / g, with an average pore size of 12.175nm and a void volume of 0.352cm 3 / g, its specific surface area data is as follows Figure 8 and as shown in Table 2. The specific surface area also decreased accordingly, and the average pore size remained stable relative to the carrier titanium dioxide.
[0074] By analyzing the specific surface area test results of Examples 1-4, it can be found that as the nickel content increases, the specific surface area continues to decrease, and the average pore size and void volume remain basically stable. In the specific surface area diagram, we can see that the carriers and catalysts of Examples 1-4 all show a standard type of isotherm IV, accompanied by an H1 hysteresis loop, which proves that the catalyst has a mesoporous structure. The formation of a mesoporous structure can also overcome the diffusion limitations of macromolecules. The IV-type isotherm reflects the process of adsorption of the mesoporous catalyst by capillary condensation after multilayer adsorption, representing the disordered distribution of the material pore structure, size and shape. The average pore size and void volume remain basically stable, indicating that the introduction of nickel and cobalt metal elements has basically no effect on the void structure in the carrier titanium dioxide, ensuring the presence of effective oil reaction sites.
[0075] Comparative Example 1
[0076] This comparative example provides a method for preparing a biofuel deoxygenation catalyst, which is a single metal catalyst containing only Co. The specific method is as follows:
[0077] 2g of cobalt nitrate was dissolved in 6mL of deionized water, placed in a magnetic stirrer, the speed was 200r / min, the stirring time was 2h, and a metal salt mixed solution was obtained. The obtained metal salt mixture was evenly stirred with 10g of nano-scale titanium dioxide, and placed in an oven at 100℃ for drying in an air atmosphere for 12h. The mixture powder after drying was transferred to a crucible and placed in a tubular furnace for further decomposition under a nitrogen environment. The decomposition temperature was set to 500℃, and the decomposition time was 4h. After the decomposition was completed, the mixture powder was crushed and sieved in a mortar to obtain a granular mixture, which was the biofuel deoxygenation catalyst. 5g of the obtained biofuel deoxygenation catalyst was weighed and placed in a three-necked flask, nitrogen was introduced (the nitrogen introduction rate was 250mL / min), 100g of catering waste oil was added, the reaction temperature was set to 350℃, and the reaction time was 2h.
[0078] The surface structure of the prepared Co catalyst was scanned by scanning electron microscopy. Fig. 9 The specific surface area tester and X-ray fluorescence spectrometer were used to analyze the particle size of the obtained catalyst and the titanium dioxide used as the carrier. The specific surface area of the catalyst was 75.38 m 2 / g, with an average pore size of 15.928nm and a void volume of 0.345cm 3 / g, its specific surface area data is as follows Fig.10 As shown in Tables 1 and 2.
[0079] By analyzing the specific surface area test results of Example 1, it can be found that the introduction of cobalt alone has a more obvious effect on the catalyst, mainly because the cobalt element directly enters the micropores on the carrier due to its small ion radius, causing the carrier nanostructure to be reconstructed, and the final average pore size has changed. The different effects on the specific surface area mainly come from the different effects on the agglomeration of nanoparticles during the decomposition process, and the cobalt element has a greater effect on the agglomeration of nanoparticles.
[0080] Comparing Example 2 with Comparative Example 1, the scanning electron microscope image of the biofuel deoxygenation catalyst prepared in Comparative Example 2 shows that the addition of different metal elements has basically no effect on the surface morphology of the catalyst. Similarly, comparing Example 2 with Comparative Example 1, it can be seen from Comparative Example 2 that the addition of different metal elements has different effects on the specific surface area of the catalyst, and the average pore size has undergone a relatively obvious change, which may be related to the small radius of the single metal ion directly entering the micropores, causing the nanostructure of the carrier to be reconstructed. Further, comparing Example 2 with Comparative Example 1, the specific surface area test results of Comparative Example 2 show that the introduction of multiple metal elements has basically no effect on the size of the void volume on the carrier.
[0081] Performance testing:
[0082] (1) Catalyst composition
[0083] The X-ray fluorescence spectrometer was used to test the biofuel deoxygenation catalysts prepared in Examples 1-4 and Comparative Example 1. The results are shown in Table 1.
[0084] Table 1: Elemental composition of biofuel deoxygenation catalysts
[0085]
[0086] (2) Catalyst structure
[0087] The surface structure and particle size of the biofuel deoxygenation catalyst prepared in the above embodiment and comparative example were analyzed by scanning electron microscope and BET specific surface area tester, and the results are shown in Table 2: Table 2:
[0088] Specific surface area, average pore size and void volume of biofuel deoxygenation catalysts
[0089] <![CDATA[BET specific surface area (m 2 / g)]]> Average pore size (nm) <![CDATA[Void volume (m 3 / g)]]> Example 1 78.081 12.281 0.353 Example 2 77.521 12.266 0.359 Example 3 74.735 12.261 0.346 Example 4 75.793 12.175 0.352 Comparative Example 1 75.28 15.928 0.345 <![CDATA[TiO2]]> 84.438 12.430 0.345
[0090] The specific surface area of the catalyst is TiO2>Example 1>Example 2>Example 4>Example 3, which shows that when the bimetallic is introduced into the carrier by impregnation, the metal element will cause the nanoparticles to agglomerate to varying degrees during the decomposition process to increase the particle size, resulting in a slight decrease in the specific surface area of the catalyst. In addition, the coverage of the support pores and the changes in the void structure after calcination may be the reasons for the reduction in specific surface area. The pore sizes of all catalysts are within the mesoporous range, and the pores within the mesoporous range will be conducive to the deoxygenation reaction. When the metal loading (20wt.%) of all catalysts is similar, it can be seen that the introduction of a higher concentration of Co element will reduce the specific surface area of the catalyst, which may be caused by agglomeration. In addition to the pore characteristics, the dispersion of active metals plays an important role in the deoxygenation activity. According to the results of XRF, the components of NiO and Co3O4 measured in the prepared catalyst are consistent with the actual components, proving that the impregnation into the carrier is successful, ensuring that the transition metal elements can successfully play the role of bond breaking and isomerization on the carrier.
[0091] Combined with Table 2 above and Figure 1-10 By comparing the scanning electron microscope images of the biofuel deoxygenation catalyst prepared in Example 1 and Comparative Example 1, it can be seen that the addition of different metal elements has basically no effect on the particle size of the catalyst. Further, by comparing the specific surface area test results of Example 2 and Comparative Example 1, it can be seen that the introduction of cobalt element has a greater impact on the specific surface area of the catalyst, which may be because cobalt element affects the agglomeration and bonding between particles.
[0092] By analyzing the specific surface area test results of the catalysts obtained in Examples 1-4 and titanium dioxide as a carrier, it can be found that as the molar ratio of nickel to cobalt increases, the specific surface area of the biofuel deoxygenation catalyst continues to decrease, and its average pore size and void volume remain basically stable. From the specific surface area diagram ( Figure 2 , Figure 4 , Figure 6 , Figure 8) can be seen that the carriers and catalysts of Examples 1-4 all show isotherms of the standard type IV, and are accompanied by H3 hysteresis loops, which prove that the catalyst has a mesoporous structure. The formation of mesoporous structure can also overcome the diffusion limitation of macromolecules. The IV type isotherm reflects the process of adsorption of mesoporous catalysts by capillary condensation after multilayer adsorption, representing the disordered distribution of material pore structure, size and shape. The selection of mesoporous supports is also crucial to ensure that relatively small nickel particles are properly impregnated into their surfaces to ensure high metallic nickel surfaces. On the other hand, microporous supports (pore size less than 2nm) may not be suitable, because even if they have a higher specific surface area, their pores may also be blocked by the nickel supports sintered therein during calcination. The catalyst relative pressure of Comparative Example 1 varies slightly between 0.7-1.0, but the adsorption amount decreases relatively, which may be due to the entry of some cobalt metal particles into the support channel in the carrier, which reduces the number of active sites of the active sites where the deoxidation and isomerization of waste grease occurs.
[0093] (3) High temperature deoxidation activity detection
[0094] The activity of the biofuel deoxygenation catalyst prepared in Examples 1-4 and Comparative Example 1 was tested. The activity evaluation of the catalyst on the deoxygenation of biofuel was carried out in a heater. The reaction conditions were: 5 g of catalyst, the raw material was waste catering oil produced after frying food, the reaction environment used was a nitrogen flow rate of 250 mL / min, the reaction pressure was normal pressure, the reaction temperature was 350° C. and 370° C., and the reaction time was 2 h. The deoxygenation effect of biofuel was calculated according to the formula: catering waste oil deoxygenation effect = (sum of peak area of alkanes + sum of peak area of olefins) / sum of total peak area × 100%. The test results are shown in Table 3.
[0095] Table 3: Deoxygenation effect of biofuel deoxygenation catalyst on biofuel produced by decomposition of oxygenated oils
[0096]
[0097] It can be seen from Table 3 above that: when the reaction temperature is 350-370°C, the deoxygenation efficiency of the catalysts of each embodiment for waste catering oils changes continuously with the change of the molar ratio of nickel and cobalt, and can reach up to 83% or more. The selectivity of biofuel conversion and hydrocarbons can be improved by adjusting the molar ratio of Ni element addition. The overall catalytic activity can be improved by forming a bimetallic bifunctional catalyst system with Co transition metal elements. The biofuel selectivity can reach up to 44.5% (NiCo (3:2)), and this catalyst also shows an efficient deoxygenation effect (83.13%). This is mainly due to adjusting the molar ratio of the bimetallic elements, improving the ability of bond breaking and isomerization, and producing a better range of hydrocarbons in biofuels.
[0098] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A biofuel deoxygenation catalyst, characterized in that: The catalyst comprises active components, a carrier and an auxiliary agent. The active components are metal nickel and cobalt, and the carrier is titanium dioxide.
2. The biofuel deoxygenation catalyst according to claim 1, characterized in that: The active components of the catalyst are made of nickel nitrate and cobalt nitrate, and the mass ratio of nickel nitrate to cobalt nitrate is (1-3):(1-2).
3. The biofuel deoxygenation catalyst according to claim 2, characterized in that: The mass ratio of metal nitrate to titanium dioxide is 1:
5.
4. The biofuel deoxygenation catalyst according to claim 1, characterized in that: The carrier is 5-10nm hydrophilic and lipophilic titanium dioxide.
5. A method for preparing a biofuel deoxygenation catalyst according to any one of claims 1 to 4, characterized in that: The steps include: (1) dissolving nickel nitrate and cobalt nitrate to obtain a metal salt mixed solution; (2) mixing the metal salt mixed solution obtained in step (1) with nano-titanium dioxide and drying them to obtain a metal salt titanium dioxide mixed powder; (3) Decomposing the metal salt titanium dioxide mixed powder obtained in step (2) under an inert gas to obtain a biofuel deoxidation catalyst.
6. The method for preparing a biofuel deoxygenation catalyst according to claim 5, characterized in that: The drying temperature in step (2) is 50-150° C. and the drying time is 10-14 hours.
7. The method for preparing a biofuel deoxygenation catalyst according to claim 5, characterized in that: The inert gas used for decomposition under inert gas in step (3) is nitrogen, the decomposition temperature is 400-600° C., and the decomposition time is 3-5 hours.
8. The method for preparing a biofuel deoxygenation catalyst according to claim 5, characterized in that: The step (1) of dissolving nickel nitrate and cobalt nitrate is specifically as follows: Nickel nitrate and cobalt nitrate are placed in a container, deionized water is added, and the mixture is stirred at a stirring speed of 100-300 r / min for 1-3 hours to obtain a metal salt mixed solution.
9. Use of the biofuel deoxygenation catalyst according to any one of claims 1 to 4 in biofuel production.
Citation Information
Patent Citations
Supported FeNi bimetallic catalyst as well as preparation method and application thereof
CN116139865A